Disappearance of the progenitor of supernova iPTF13bvn - Folatelli, Gaston (2016)
Supernova (SN) iPTF13bvn in NGC 5806 was the first Type Ib SN to have been tentatively associated with a progenitor in pre-explosion images. We performed deep ultraviolet (UV) and optical Hubble Space Telescope observations of the SN site ˜740 days after explosion. We detect an object in the optical bands that is fainter than the pre-explosion object. This dimming is likely not produced by dust absorption in the ejecta; thus, our finding confirms the connection of the progenitor candidate with the SN. The object in our data is likely dominated by the fading SN, implying that the pre-SN flux is mostly due to the progenitor. We compare our revised pre-SN photometry with previously proposed models. Although binary progenitors are favored, models need to be refined. In particular, to comply with our deep UV detection limit, any companion star must be less luminous than a late-O star or substantially obscured by newly formed dust. A definitive progenitor characterization will require further observations to disentangle the contribution of a much fainter SN and its environment.